GREEN BANKING, BOARD DIVERSITY, AND BANK PERFORMANCE: A LINIEAR AND NON-LINEAR STUDY IN INDONESIA - Septian Yudha Kusuma; Ida Nurhayati; Mella Katrina Sari; Tri Wahyudi (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2026)
The pressure on the banking sector to embrace sustainability principles stems not only from domestic regulations but also from the fact that economic activities have become urgent concerns for governments and businesses across all industries. This study aims to examine the influence of green banking and board diversity on bank profitability, considering the possibility of nonlinear relationships. Using 39 banks with a 3-year observation period obtained 117 panel data observations, this study uses a Random Effects model with a robust clustered standard errors approach. The results study show that green banking has proven insignificant for profitability. In contrast, non-linear board diversity has been shown to have a u-shape influence, and the linear influence is not significant on profitability. This result is a marker that board diversity are important components in achieving bank performance, meanwhile, green banking has not had a significant impact. The results also support the theory of upper echelons and self-categorization